A characterization for B-singular integral operator and its commutators on generalized weighted B-Morrey spaces - Hasanov, J.J.; Ekincioglu, I.; Keskin, C. (Carpathian Mathematical Publications, 2023)
We study the maximal operator M_γ and the singular integral operator A_γ, associated with the generalized shift operator. The generalized shift operators are associated with the Laplace-Bessel differential operator. Our analysis is based on two weighted inequalities for the maximal operator, singular integral operators, and their commutators, related to the Laplace-Bessel differential operator in generalized weighted B-Morrey spaces.